STUDI KORELASI MUAI SUSUT TANAH EKSPANSIF DI DAERAH KARAWANG DAN CIKARANG - Steven; Andryan Suhendra (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2023)
Expansive soil is a soil that easily expands and shrinks when there is a change in moisture content. The nature and characteristics of expansive soil have a dangerous impact on building structures such as foundation failure and cracking. This research will approach the correlation of soil parameters that have not been tested in the laboratory to obtain values that are close to field tests. In addition, it classifies the soil type into a certain level of expansiveness based on the approach taken. In this study, it was found that the expansive soils in each project have a development potential of